Acute pulmonary oedema in chronic dialysis patients, causes, clinical course and outcome admitted into emergency department - P. A., Jimnaz; Abdul Kharim, Ajmal (International Journal of Advances in Medicine, 2017)
Background: Chronic dialysis (CD) patient are at increased risk of multiple organ dysfunction. Recent study, estimated that 2% of CD patients require intensive care unit (ICU) admission every year. Acute Pulmonary Oedema is major cause for ICU admissions, objective of the study is to determine the cause, clinical course and outcome of APO in CD patients admitted in Intensive Care Units under Emergency Department. Methods: Prospective and observational study conducted for 1 year in our institute, a tertiary care centre, was done on chronic dialysis(CD) who presented with Acute pulmonary oedema(APO) for determine cause for APO, severity of outcome by APACHE II and sofa score. Data was entered in Microsoft Excel spread sheet and analyzed using SPSS software. Descriptive analysis and chi square test was done. Results: Study included 100 CD patients. Main etiologic factor of CKD was T2DM 56%. Etiology of APO in this study showed as 34% are due to excessive interdialytic weight gain. Only 4 patients were assessed by SOFA score and high sofa score no patients had expired. Study showed survived patients got mean APACHE II score of 24±3.4 and expired patients got mean APACHE II score of 32.9±2.5, with a significant P value <0.001. Conclusions: Main etiology of APO in CD patients were excessive interdialytic weight gain 34 %. APACHE II score as outcome predictors. APACHE II score of more than 30 have poor outcome